Co-design of a Voice-Driven Interactive Smart Guide for Museum Accessibility and Management - Wang, Xi (Journal of Audiovisual Translation, 2024)
This paper describes the process of co-designing and creating a voice-driven interactive smart audio descriptive guide for Titanic Belfast, a world-leading tourist attraction. This smart audio descriptive guide is intended to enhance museum accessibility and visitor experience, especially for blind and partially sighted (BPS) visitors. A key research question is to explore to what extent museums can conveniently produce their own smart guide to enrich the visitor experience for BPS visitors. The paper first outlines the necessarily complex set of team functional roles and users in designing the smart audio descriptive guide and then presents the main challenges and opportunities arising from the key user requirements from both BPS visitor and the Museum Management perspectives. The main design features of the smart audio descriptive guide, which address these requirements, are then described. The paper then outlines the main findings of our evaluative review of the smart guide with a group of BPS participants and from a Museum Management perspective. One of the key benefits of our approach is that the smart audio descriptive guide has the potential to offer museums and cultural venues a new, affordable approach to providing and maintaining a high-quality accessibility experience with lower design effort than traditional audio descriptive guide approaches. Lay summary: I developed a voice-driven interactive audio descriptive guide specifically for Titanic Belfast, one of the leading tourist attractions globally. The audio descriptive guides are commonly used in museums to provide verbal description of visual information for blind and partially sighted (BPS) visitors. Most of these guides are keypad based and cannot answer questions from visitors. My innovative guide is designed with the aim to incorporate some new features such as voice driven and chat function, to enhance accessibility and visitor experience, primarily for BPS people. The creation of this guide involved a detailed process where the needs of the BPS visitors and museum management were carefully considered to address various challenges and seize opportunities to enhance accessibility. Key design features of the guide were developed to meet these specific needs, making the museum experience more inclusive. An evaluation conducted with BPS participants has shown some promising results. The new guide not only meets their needs effectively but also offers an affordable solution for museums. This approach reduces the effort and cost typically required to create an audio descriptive guide, presenting a sustainable option that could be adopted by other cultural venues looking to improve accessibility and visitor engagement.